Indonesian mothers' perception about the children nutritional status and its related factors - Neli, Wa; Latif, Fillya Light A; Rompas, Helviani; Putri, Atika Hervina; Firman, La Ode Muhammad (Public Health of Indonesia, 2021)
Background: Nutrition problems are the main public health issues in developing countries, including Indonesia. Malnutrition will lead to failure of physical growth and development of intelligence, decreased work productivity, and reduced endurance resulting in increased rates of pain and death. Therefore, mothers have an essential role in the prevention of nutritional disorders in children.Objective: To compare the nutritional status of primary school children based on maternal assessment and anthropometry measurements and analyze factors that influence the mother's misperceptions about the nutritional status of the children.Methods: A cross-sectional research design was used. A total of 96 mothers of elementary school students were included. Quota sampling was used in selecting samples based on population characteristics. Children's nutritional status was classified according to WHO anthropometry standards 2006 for children aged 5-18 years based on age and gender. The mother's perception of the child's nutritional status was measured using an online validated questionnaire (Google Form). Descriptive and bivariate statistics were used for data analysis.Results: 56.2% of mothers gave an appropriate assessment of the nutritional status of the children. Education and work significantly influenced the accuracy of the mother's perception of their children's nutritional status. A total of 38.4% of mothers with high school education levels misjudged their child's nutritional status compared to those who did not finish high school (p = 0.058). Also, 56.3% of non-working mothers were wrong in assessing their child's nutritional status compared to working mothers (p=0.014).Conclusion: The results of this study can be used to improve the knowledge and skills of mothers in assessing the nutritional status of children as one of the strategies to reduce the incidence of malnutrition in children.